Characterization of Pregelatinized, Pentanol and Acetylated Modified Primary Starch - Desy Nawangsari; Rani Prabandari; Dina Febrina (LPPM Universitas Harapan Bangsa, 2024)
Tablets are pharmaceutical preparations consisting of active ingredients and excipients. One of the commonly used excipients is starch. (Colocasia esculenta (L). Schott var, Pratama) is a plant that contains a high source of starch. The use of natural starch in tablets has limitations in the form of less fast flow and poor compressibility. The purpose of this study was to modify natural starch by pregelatinization, pentanol and acetylation. This research was conducted using laboratory experimental methods, starting with sorting the starch tubers of (Colocasia esculenta (L). Schott var, Pratama), starch isolation, modification and characterization of the resulting starch. The characterization results showed that the flow rate of natural starch, pregelatinized, pentanol and acetylated sequentially was 1.9 ± 0.19; 2.15 ± 0.37; 1.35 ± 0.15; and 1.95 ± 0.14 g/s with an angle of repose of 20.49 ± 1.99; 17.12 ± 1.99; 22.92 ± 1.18 and 20.06 ± 1.97°, while the compressibility value is 20.23 ± 5.31; 15.47 ± 3.03; 21, 09 ± 2.8 and 19.09 ± 2.05%.